2023
DOI: 10.3390/foods12101951
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic Fermentation as a Source of Congeners in Fruit Spirits

Abstract: Fermentation is a crucial process in the production of alcoholic beverages such as spirits, which produces a number of volatile compounds due to the metabolic activities of yeast. These volatile compounds, together with the volatile components of the raw materials and the volatile compounds produced during the distillation and aging process, play a crucial role in determining the final flavor and aroma of spirits. In this manuscript, we provide a comprehensive overview of yeast fermentation and the volatile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…By considering all of these factors, the food chain can become more sustainable by TA B L E 3 The influence of red berry, variety, and yeast on the volatile profile of strawberry, raspberry, and blueberry wines. Note: Concentration and threshold (Stanzer et al, 2023) of each compound are expressed in µg/L, and the aroma descriptors of the major compounds are also described. Adapted from the works of ), Feng et al (2015, Liu et al (2019), andSong et al (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By considering all of these factors, the food chain can become more sustainable by TA B L E 3 The influence of red berry, variety, and yeast on the volatile profile of strawberry, raspberry, and blueberry wines. Note: Concentration and threshold (Stanzer et al, 2023) of each compound are expressed in µg/L, and the aroma descriptors of the major compounds are also described. Adapted from the works of ), Feng et al (2015, Liu et al (2019), andSong et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, fruit spirits are colorless, except for those that are aged in wooden barrels, and feature a particular fruit aroma. Chemically, the major components of distilled spirits are ethanol and water, but other elements such as higher alcohols, esters, aldehydes, methanol, volatile phenols, and organic acids are also present (Buglass, 2011;Stanzer et al, 2023). The volatile profile, a main factor influencing the sensory properties of the fruit spirits, depends on various factors, including the type and quality of the fruit, conditions of the alcoholic fermentation, and storage conditions.…”
Section: Red Berry Spirits-strawberry Raspberry and Blueberrymentioning
confidence: 99%
“…During different technological processes of food production, a so-called secondary aroma is forming. The most important types of food processes responsible for the synthesis aroma compounds in food are fermentation [13] and non-enzymatic processes resulting from thermal treatments [14]. Some foods require more than one technological process, and they are the source of a great number of various aroma components.…”
Section: What Is Aroma In Generalmentioning
confidence: 99%
“…Spirit cuts at <60% ABV later on during the distillation are thought to enhance phenol and guaiacol congener concentrations as they have lower volatility [11]. The spirit cut (middle fraction) is dominated by short to medium carbon chain (C5-C14) fatty acid ethyl esters, such as ethyl hexanoate, ethyl octanoate, ethyl decanoate, ethyl dodecanoate, and ethyl lactate [73,105]. Goss et al identified that the predominant fatty acid ethyl esters in Scotch whiskies were medium chain (C8-C14), with esters of >C14 in trace amounts as their solubility decreases with increasing carbon chain length, but also due to the fact that mainly short/medium chain ethyl esters are generated during fermentation [106].…”
Section: Congeners By Volatilitymentioning
confidence: 99%